Restitution of tax which has been paid under mistake of law - Md Abdul Jalil, (Fakulti Undang - Undang, 2010)
The court in the UK in 1802 applied the legal maxim ignorantia juris non excusat (which means ‘ignorance of law is no excuse’) in Bilbie v Lumley case which was involved in recovery of indemnity mistakenly paid by an insurance company to the insured. In this case the court held that insurance indemnity paid to the insured under mistake of law is not refundable because of the above maxim. In later cases courts in England also applied the above legal maxim in tax cases barring taxpayers from recovering tax paid under mistake of law. So, the above legal maxim became the English common law rule in almost every later case involving payment made under mistake of law. It is to be noted that the above legal maxim was originally developed to be applied in criminal cases. It seems that the above maxim of law was misapplied by the court in the Bilbie case in indemnity refund claim and other courts also misapplied the maxim in tax restitution cases. That maxim is acceptable in criminal cases but it is not applicable or desirable in recovery of money or tax paid under mistake of law. Hence, the House of Lords after almost two hundred years has overruled the Bilbie decision in Kleinwort Benson Ltd v Lincoln City Council, decided in 1998